Verbal modifiers in areal perspective: The case of Latvian Romani - Kozhanov, Kirill; Ross, Anette (Kalbotyra, 2022)
Based on the analysis of the texts collected in the 1930s in Latvia and Estonia, this paper provides a description of the semantics of the verbal modifiers, i.e., prefixes (preverbs) and particles, in Latvian Romani. The system of verbal modifiers in Latvian Romani is an innovation evolved under Slavic and Baltic influence. Most preverbs are instances of MAT-borrowing from Slavic and Baltic, whereas verb particles are a PATborrowing, modelled after the Latvian system. The paper argues that even preverbs of Slavic origin often copy the semantics and derivational patterns of Latvian prefixed verbs. It is also shown that, differently from Latvian, in Romani both preverbs and verb particles can affect the verb’s argument structure (e.g., by making it transitive) and change its aspectual value (e.g., by making it perfective). Finally, the distribution of verbal modifiers in Latvian Romani (the development of verb particles as opposed to other closely related Northeastern Romani dialects which only have prefixes, and higher frequency of verb particles in Estonia than in Latvia) confirms the areal cline in the spread of verb particles.
Keywords: Romani; verbal prefixes; preverbs; verb particles; Latvian; Slavic; language contact